IMPLEMENTASI PEMBELAJARAN MENGGUNAKAN MODEL KOOPERATIF TIPE STAD BERBANTUAN MEDIA QUIZIZZ UNTUK UPAYA MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI HUKUM NEWTON KELAS X SMA - Karismara Olivya Afiva Jothy; Zuhdi Ma’aruf; Muhammad Syafi’i (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: Learning outcomes are results that must be achieved after the learning process takes place. One aspect of learning outcomes is cognitive learning outcomes. The purpose of this study was to determine the effect of the application of the STAD type cooperative learning model assisted by Quizizz media on students' cognitive learning outcomes. The type of research used is experimental research with a quasi-experimental design